Communication between parents and preschool-aged children about tuberculosis preventive treatment: A qualitative study - Windy Rakhmawati; Siti Yuyun Rahayu Fitri; Aat Sriati; Sri Hendrawati (Wolters Kluwer Medknow Publications, 2022)
Background: Communication with preschool-aged children about Tuberculosis Preventive Treatment (TPT) is a challenge for parents. Good communication can encourage children to be involved in their treatment and enhance their adherence to the treatment. This study aimed to explore the experience of parents in communicating with their preschool-aged children about TPT. Materials and Methods: This study used a qualitative approach. Participants were 10 parents who were selected using the purposive sampling technique from three community health centers in Bandung City, Indonesia. The inclusion criteria for the study were parents who have a child aged 3-5 years who received or was receiving TPT. Semi-structured interviews were conducted to obtain the data, and when saturation was reached, no further interviews were conducted. Subsequently, the interviews were transcribed and analyzed using thematic analysis. Results: The findings revealed three themes with eight categories. The themes were persuading children, lack of understanding, and supporting communication. Conclusions: The findings are relevant for nurses and other health professionals who need to provide adequate information related to TPT and to develop media for parents and children during their communication. Nurses can collaborate with other physicians and software engineers to develop interesting media such as game applications to educate children about Tuberculosis (TB) prevention.